Teaching Writing Narratives Online by Using Storyboard Technique During the Lockdown period of the Virus Covid-19 Outbreak - Edi Pujo Basuki; Tiyas Saputri (Institut Agama Islam Negeri Palopo, 2020)
Living among the virus covid-19 epidemic, lecturing was conducted online. One such learning technique is the storyboard technique. The media picture (storyboard) is a media that is a reproduction of the original form in dimensions, in the form of photographs or paintings. Storyboard technique is activity before writing that emphasizes the elaboration (detailed explanation) predictions or estimates, the growth of ideas, and sequencing. This study aims to (1) describe the process of pre- developing of a storyboard, (2) show a model of the sequence of the story of storyboard (3) show an inspiring lesson plan of teaching writing of narrative text online using storyboard technique. The design of this study is descriptive qualitative. The design of this study is descriptive qualitative. The research framework is semantic construction, specifically limits the focus on coherence. The construction of the pre-developing of the storyboard is built on two concepts: building the coherence theory of van Dijk's building text and the generic structure of the narrative text. The result of this study are (1) In order to produce a storyboard in creating narrative text, the teacher should simplify the global coherence of complex story to the local one, after that it is continued by the technique of visualization as following the generic structure of a narrative text (2) The storyboard is drawn digitally (3) The lesson plan of teaching using this technique